Agro & Physics - A proposal to understand physics through equipment in the rural area - Benevenuto , Gilmar Alves; Noronha , Aurélio Wildson Teixeira de (Seven Editora, 2023)
The present work aims to report the experience of the science fair entitled Agro &Physics held by the professor, monitor and students of the General Physics class for the Agronomy Course of the University of the International Integration of Afro-Brazilian Lusophony (UNILAB) in the semester 2019.1. Science fairs are spaces for scientific initiation, in which students and teachers mount demonstrative exhibitions (DORNFELD, 2011). DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-097